2023
DOI: 10.1038/s41537-023-00353-0
|View full text |Cite
|
Sign up to set email alerts
|

What are the barriers and facilitators of clozapine use in early psychosis? A survey of UK early intervention clinicians

Abstract: Clozapine is the most effective medication for treatment-resistant psychosis, but evidence points to substantial underuse, especially within early intervention psychosis (EIP) services. We explored clinicians’ views on perceived barriers and facilitators to offering patients clozapine within EIP services. A cross-sectional survey was distributed electronically to clinicians practising in EIP services across England. A mixed methods approach was used to assess barriers to clozapine, and attitudes and opinions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous research has looked at clinician attitudes to clozapine prescription [ 2 , 9 , 17 ]. The main perceived barriers to clozapine use in early intervention for psychosis services included patient concerns about side effects and physical health monitoring requirements [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has looked at clinician attitudes to clozapine prescription [ 2 , 9 , 17 ]. The main perceived barriers to clozapine use in early intervention for psychosis services included patient concerns about side effects and physical health monitoring requirements [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has looked at clinician attitudes to clozapine prescription [ 2 , 9 , 17 ]. The main perceived barriers to clozapine use in early intervention for psychosis services included patient concerns about side effects and physical health monitoring requirements [ 9 ]. A 2005 study involving CAMHS consultants across the United Kingdom’s clozapine prescription practice concluded that unfamiliarity with the drug and the need for monitoring of side-effects seem to negatively influence use, and it might be that clearer information about effectiveness and prescribing practices would result in increased usage [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation